2016
DOI: 10.1016/j.rbre.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian multicenter study of 71 patients with juvenile-onset Takayasu's arteritis: clinical and angiographic features

Abstract: This is the largest study on juvenile-onset Takayasu arteritis, and a high number of patients under the age of 10 years, with predominance of constitutional symptoms early in the disease, was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 17 publications
1
16
0
2
Order By: Relevance
“…Characteristic features of the late, occlusive phase are limb ischemia or absent pulses, vascular bruits, hypertension as a consequence of renal artery stenosis or aortic narrowing and aortic fibrosis, mesenteric angina, retinopathy, aortic regurgitation and neurologic symptoms secondary to hypertension or ischemia. An aortic valve insufficiency and congestive heart failure has been reported in a significant proportion of patients [6,[21][22][23][24][25][26][27][28] The current EULAR/PRINTO/PRES validated classification criteria for childhood Takayasu arteritis are characterized by high sensitivity and specificity assessed as 100% and 99.9%, respectively [7]. The mandatory criterion is the typical angiographic abnormality of the aorta or its main branches and pulmonary arteries found in angiography (conventional, CTA or MRA): aneurysm/dilatation, narrowing, occlusion or thickened arterial wall not due to fibromuscular dysplasia, or similar causes, usually focal or segmental.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristic features of the late, occlusive phase are limb ischemia or absent pulses, vascular bruits, hypertension as a consequence of renal artery stenosis or aortic narrowing and aortic fibrosis, mesenteric angina, retinopathy, aortic regurgitation and neurologic symptoms secondary to hypertension or ischemia. An aortic valve insufficiency and congestive heart failure has been reported in a significant proportion of patients [6,[21][22][23][24][25][26][27][28] The current EULAR/PRINTO/PRES validated classification criteria for childhood Takayasu arteritis are characterized by high sensitivity and specificity assessed as 100% and 99.9%, respectively [7]. The mandatory criterion is the typical angiographic abnormality of the aorta or its main branches and pulmonary arteries found in angiography (conventional, CTA or MRA): aneurysm/dilatation, narrowing, occlusion or thickened arterial wall not due to fibromuscular dysplasia, or similar causes, usually focal or segmental.…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the role of Mycobacterium tuberculosis in patients diagnosed with Takayasu's arteritis, we studied 13 previously published articles, which in total included 196 patients diagnosed with Takayasu's arteritis [11,16,17,[19][20][21][22][23][24][25][26][27][28]. Out of which 68 had either a prior or current tuberculous infection [11,16,17,[19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Over many years, many studies show shreds of evidence implicating the contribution of Mycobacterium tuberculosis in the pathogenesis of TAK [ 21 ]. Our studies found 65 cases of latent tuberculosis in patients diagnosed with TAK [ 11 , 16 , 17 , 19 - 23 , 26 , 28 ]. We discovered that the majority of these observational studies detected latent tuberculosis in a patient diagnosed with TAK.…”
Section: Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…Out of the 71 patients selected in the study, 51 of them were girls, showing a higher prevalence in female population. The most frequent finding in laboratory testing was an ESR elevation (9).…”
Section: Discussionmentioning
confidence: 99%